Synthesis, characterization and antibacterial activity of cu(II) and ni(II) complexes of 3,4,5-trimethoxybenzoyl thiourea ligands - Norsyafikah Asyilla, Binti Nordin (Universiti Malaysia Sarawak, UNIMAS, 2012)
In this study, Cu(II) and Ni(II) complexes of thiourea ligands have been synthesized. The synthesized thiourea ligands were different according to the types of amino acids used which are glycine and phenylalanine. The thiourea ligands and their complexes were characterized using FTIR, UV/Visible, 1H and 13C NMR spectroscopic methods, CHN microelemental analysis, molar conductivity and melting points. The FTIR stretching vibrations of the complexes showed significant shift compared to the stretching vibrations for the ligands. The n→π* transition were shown for the ligands and π →π* transition were observed for the complexes. For 1H and 13CNMR, the spectra of the complexes were shifted from the spectra of the ligands. The proposed structures for the complexes were square planar and the ligands were coordinated to the metals through the carboxylate group. Complex (3) showed significant activity towards the growth of E. coli with the MIC value of 92.5 ppm.